$1!Wm!GW!Pp3G{s - Yu, Yonghe, active 1691-1697 (Salt Lake City, UT : Project Gutenberg, 2017)
"$1!Wm!GW!Pp3G{(B" by Yonghe Yu is a historical account written in the late 17th century. The work chronicles the author$1 (Bs travel experiences and observations as he navigates through various regions in Taiwan and encounters local cultures, landscapes, and the political climate of the time. This autobiographical journey provides insights into the natural beauty, challenges of travel, and interactions with indigenous peoples. The opening of the text sets the stage for the author's travels that commence in Fujian province and extend to Taiwan, highlighting numerous locations he visits and the experiences he gathers along the way. The narrative conveys a mix of poetic reflections, descriptions of geographical features, and social encounters, including his interactions with local officials and indigenous communities. These segments offer a vivid portrayal of the landscape, as well as the flora and fauna encountered, while also hinting at the complexities of human relationships and the challenges posed by nature and society during his quest. (This is an automatically generated summary.)s
Release date is 2017-05-06
Produced by Miaoyin Lin
Keywords: Taiwan -- Description and travel; Yu, Yonghe, active 1691-1697 -- Travel; Taiwan -- Social life and customs; Taiwan -- History -- 17th century